After the New Order : Space, Politics, and Jakarta - Kusno, Abidin, 1966- (Book collections on Project MUSE., 2014)
Examines the factors behind the Indonesian military's decision to reposition its dominant role in the country's socio-political affairs after the fall of Suharto. It covers the contests between the military and the new civilian regime under President Wahid over its altered role, and the part played by the military in his fall. In addition, the military's future role under President Megawati is assessed.